Length-weight relationship and condition factor of freshwater crab Barytelphusa gurini, (Decapoda, Brachyura). - Patil, Kalpana M; Patil, Meena U (Journal of Experimental Sciences, 2012)
The length-weight relationship and condition factor of Barytelphusagurini was studies. The exponent ‘b’, value for males 2.83 and for females it is2.03, and combined crabs is 2.35. Growth generally shows negative allometry in all crabs. The condition factor (K) for male is 0.000802, for female is 0.000669 and for combined sexes is 0.000214. The regression revealed high correlation andthe coefficient of determination (r2) for male is 97.8%, in female it is 98.6%, which is very close to 1, and in combined crabs it is 93.7%.